A Brief Review on Apoptosis - Sharma, Ankit; SHARMA, RANU; SINGH, SURYA PRATAP; KHINCHI, M. P. (Asian Journal of Pharmaceutical Research and Development, 2018)
Apoptosis is a cell death mechanism characterized by depolymerization of cytoskeleton, cell shrinkage, chromatin condensation, nuclear fragmentation and translocation of phosphatidylserine to the cell surface. This process is therefore called programmed cell death. Between 50 and 70 billion cells die each day due to apoptosis in the average human adult. Apoptosis and necrosis are considered to be distinct modes of cell death; however, apoptosis can progress to secondary necrosis if apoptotic cells are not efficiently removed by phagocytic cells. During the last decade, exceptional for the basic research, the apoptosis have attracted many attentions due to its potential application in therapying the various human diseases. . In diseases caused by deficient apoptosis, such as cancer, viral latency and autoimmunity, methods of producing selective apoptosis are being sought